The Influence of Short-Duration Video Content on Short-Term Memory in Junior High School Students: (A Study of 30 Students at Yayasan Irtiqo Kebajikan) - Aline Azkiya; Azzahra Salwa Ardina; Khalisha Naura Polla; Raisah Shabrina (JURNAL RISET RUMPUN ILMU KESEHATAN, 2024)
The increasing consumption of short-form video content, such as TikTok, Instagram Reels, and YouTube Shorts, has raised concerns regarding its impact on cognitive functions, particularly short-term memory. This study aimed to examine the effect of short duration video exposure on short-term memory performance among students at Yayasan Irtiqo Kebajikan. An experimental method with a two-group design was employed, consisting of an experimental group that watched short duration videos for 180 seconds and a control group that received no video exposure prior to the memory test. The participants were 40 students selected through random sampling. Short-term memory was measured using the ME Test, a subtest of the Intelligenz Struktur Test (IST), which assesses the ability to recall a series of words. The results of statistical analysis indicated a significant difference between the experimental and control groups (p < 0.05), with the experimental group demonstrating lower short-term memory scores. These findings suggest that exposure to short-form video content may negatively affect individuals ability to store and process information in short-term memory, highlighting the importance of managing digital media consumption among children and adolescents.